On the spectrum and fine spectrum of an upper triangular double-band matrix on sequence spaces - Ercan, Sinan (Semnan Univ, 2021)
In this paper, we investigate the spectrum and fine spectrum of the upper triangular double-band matrix Delta(uv) on cs sequence space. We also determine the approximate point spectrum, the defect spectrum and the compression spectrum of this matrix on cs.
Keywords: Spectrum of an operator; sequence space